Nanoparticles Synergistic Effect with Various Substrate Pretreatment and their Comparison on Biogas Production from Algae Waste - Asad A. Zaidi; Sohaib Zia Khan; Hamad Almohamadi; Essam R. I. Mahmoud; Muhammad N. Naseer (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Algae waste is one of the potential substrates for biogas and biohydrogen production and can comprehend multiple benefits of waste treatment and resource utilization. In view of the key bottlenecks such as low substrate degradation rate and poor productivity of algae waste production process, this study analyzes the combined effect of two metallic and metallic oxide nanoparticles with different substrate pretreatment methods (autoclave, ultrasonic, and microwave methods) to investigate the effect of anaerobic digestion of green algae (Enteromorpha). The results showed that out of the three pretreatment methods, microwave pretreatment and nanoparticles' synergistic effect significantly increases biogas production. The microbial community composition at the phylum level was analyzed. It was observed that the Firmicutes were most abundant across all samples. The relative abundance of Firmicutes for control, Ni NPs + MW, Co NPs + MW, and Fe3O4 NPs + MW groups were 51.78, 70.37, 75.77, and 83.93%,      respectively. The second most abundant was of Bacteroidetes that also contributes to hydrogen production. This relatively high abundance of Firmicutes and Bacteroidetes promises its potential applications in a hydrogen production facility. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).